Complex repair kinetics of DNA strand breaks induced by gamma-rays of UV radiation in Ehrlich ascites tumour cells - Mlejnek, P; Kozubek, S (Radiation and environmental biophysics, 1996)
Fluorometric analysis of DNA unwinding (FADU)-a sensitive technique for the detection of strand breaks in DNA-has been modified and used for the detailed investigation of repair kinetics of DNA-strand breaks arising under different conditions in Ehrlich ascites tumour (EAT) cells irradiated by gamma-rays or ultraviolet (UV) radiation. The repair kinetics of DNA-strand breaks induced in EAT cells by gamma-radiation was measured at radiation doses of 8, 20 and 50 Gy. We found complex repair curves in all cases, probably reflecting the combined processes of break rejoining and break generation during repair. In order to affect the above-mentioned processes, we have used different conditions of repair and different types of radiation. Lowering of the temperature of incubation and treating the cells by 5-fluoro-2'-deoxyuridine (FUdR) lead to complex changes of the repair curve with a reduced "wave" pattern. In order to change the type of damage to DNA, we used UV radiation (254 nm, 10 and 20 J/m2). Detailed studies of the repair kinetics showed that the repair curve for 10 J/m2 had a second maximum within 70 min after irradiation.
Keywords: oprava DNA; Kinetics; ultrafialové záření; kinetika; Dose-Response Relationship, Radiation; DNA Repair; DNA Damage; záření gama; Carcinoma, Ehrlich Tumor; Gamma Rays; Animals; vztah dávky záření a odpovědi; Ehrlichův tumor; zvířata; poškození DNA; DNA; kalibrace; Calibration; Ultraviolet Rays